Studi Potensi Penyemaian dan Pembibitan Tanaman Mengkudu pada Beberapa Komposisi Media Tanam - Djoko Eko Hadi Susilo; Mohammad Hertos; Fahruddin Arfianto (Anterior Jurnal, 2014)
The purpose of this research is to know and find the growth potency on the seeds germination and seedling growth of Morinda plant from seed on the kind of plant media composition from March to June 2014 in Panarung, Palangka Raya. This experiment used single treatment with randomized complete design, each treatment was repeated ten times. The treatment consist of single factor is kind of plant media composition in five mixture composition and ratio : s1 = mixture of mineral soil + peat soil + ash + organic fertilizer (1:1:1:1), s2 = mixture of mineral soil + ash + organic fertilizer (1:0,5:0,5), s3 = mixture of peat soil + ash + organic fertilizer (1:0,5:0,5), s4 = mixture of mineral soil + ash + organic fertilizer (1:1:1), and s5 = mixture of peat soil + ash + organic fertilizer (1:1:1). Variable response of this research is a time of germination, the percentage of seeding, height of the plant, number of leaves, the diameter of the stem, and leaf area on 12 weeks after seeding. The experiment resulted, showed that plant media composition is very significant to high plant and leaf area seeding of morinda, but not significant to a number of leaf and diameter of stem on 12 weeks after seeding. Plant media composition that mixture of peat soil + ash + organic fertilizer (1:1:1) is the best treatment to support germination and increase seedling growth.